Jangan panik saat anak sakit / Rachma S. Sutrisno dan Umi Setyowati; Penyunting, Chrisna Farmadiani - RACHMA S. Sutrisno; Umi Setyowati; CHRISNA Farmadiani (Trans Idea Publishing, 2013)
216 hlm. : ilus ; 19 cm